Pelatihan Pemasaran Digital untuk Meningkatkan Keterampilan Pelaku UMKM di Desa Srumbung Magelang - Betari Maharani; Arinda Lovita Fendisty; Ulfa Luthfiana Masjidin; Dwi Ardiyan; Nita Dian Rizky; Nur Hidayah (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2021)
There are 26 Micro, Small, and Medium Enterprises (MSMEs) in Srumbung Village registered at the village office. However, not all MSMEs run well. Most of the MSMEs players have limited knowledge and skills in using information technology. Meanwhile, information technology for MSMEs players is critical, especially since the emergence of the Covid-19 and the implementation of the PSBB (Pembatasan Sosial Berskala Besar) policy. The existence of MSMEs will be hampered or slumped if they do not utilize technology in their business. Therefore, this society's dedication aims to improve the knowledge and skills of MSMEs players on utilizing Facebook and Instagram as online marketing tools. Society dedication was conducted from October 20, 2020, to November 5, 2020. The participants are 4 MSMEs, consist of Jenang & Krasikan, Keripik Pegagang, Sagon Kering dan Manisan Salak. The method used is education (socialization) about online marketing and operating and management training of Facebook and Instagram. This society's dedication is the increase of knowledge and skills of participants in operating and managing social media Facebook and Instagram as digital marketing media.